A Quantitative Model of Supply Chain Disruption Propagation Dynamics - Shudong Liu; Shili Xiang; Lu Wang (Engineering Proceedings)
Supply chain disruptions caused by natural disasters and human-made incidents have inflicted substantial losses on numerous companies. The management of supply chain risks, including disruption risk, has garnered significant attention from both academia and industries over the past few decades. Companies must develop effective solutions for disruption risk management. To seek an effective solution with disruption event monitoring and mitigation plans, we investigated the mechanisms and dynamics of disruption propagation along the supply chain. Specifically, we developed a quantitative mathematical model for the entire supply chain using system dynamics to understand the characteristics of disruption propagation, such as time spent for the disruption from the event location to a focal company and its impact. The model provides important management information on the development of a disruption monitoring system to enhance the resilience and robustness of supply chains, develop mitigation strategies, and minimize the adverse effects of disruptions.